2017
DOI: 10.1001/jamaophthalmol.2017.2199
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Intraocular Bleeding With Novel Oral Anticoagulants Compared With Warfarin

Abstract: IMPORTANCE It is unclear if the risk of intraocular bleeding with novel oral anticoagulants differs compared with warfarin.OBJECTIVE To characterize the risk of intraocular bleeding with novel oral anticoagulants compared with warfarin.DATA SOURCES A systematic review and meta-analysis was undertaken in an academic medical setting. MEDLINE and ClinicalTrials.gov were searched for randomized clinical trials published up until August 2016. This search was supplemented by manual bibliography searches of identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 40 publications
1
27
1
2
Order By: Relevance
“…intraocular bleeding, all the NOACs showed a lower risk of bleeding than did warfarin. This is similar to previous cohort studies which reported a reduced risk for intraocular bleeding 9,15 . Few guidelines have addressed the issue of anticoagulant use for treatment of retinal vascular occlusions and the possible risk for intraocular bleeding 21,26 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…intraocular bleeding, all the NOACs showed a lower risk of bleeding than did warfarin. This is similar to previous cohort studies which reported a reduced risk for intraocular bleeding 9,15 . Few guidelines have addressed the issue of anticoagulant use for treatment of retinal vascular occlusions and the possible risk for intraocular bleeding 21,26 .…”
Section: Discussionsupporting
confidence: 92%
“…A cohort study reported that the incidence of intraocular bleeding was less in NOAC (dabigatran and rivaroxaban) users compared to that of warfarin users 9 . Other meta-analyses also revealed a lower risk of intraocular bleeding with NOAC use 14,15 , suggesting the safety of NOAC for intraocular bleeding.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Patients with atrial fibrillation and venous thromboembolism have similar benefits. The results of the study are instructive for the selection of anticoagulant drugs in patients with high risk of retinal and subretinal hemorrhage, and preference should be given to NOACs during perioperative period (Sun et al, 2017). Furthermore, some investigators investigated the correlation between anticoagulants (warfarin vs NOACs) and death from intracerebral hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence of the association between NOAC treatment and intraocular bleeding remains inconsistent; to date, no analyses have been conducted to simultaneously and head-to-head compare the rates of intraocular bleeding in patients on the different NOAC agents versus and traditional anticoagulation. Two predominant meta-analyses on this topic, by Caldeira et al 1 and Sun et al ,2 unfortunately present contradictory findings; Caldeira et al found no difference in the risk of substantial intraocular bleeding between NOACs and traditional anticoagulation, whereas Sun et al claimed risk reductions of up to 20% in NOAC cohorts. The analyses are primarily hindered by the pooling of NOACs, which obscures the individual NOAC subgroup outcomes, in addition to heavily using data from inadequately powered trials.…”
Section: Introductionmentioning
confidence: 99%